ANALISIS BEBAN SEISMIK PADA STRUKTUR GEDUNG ONKOLOGI RUMAH SAKIT UMUM HAJI SURABAYA BERDASARKAN SNI 1726:2019 (STUDI KASUS: PROYEK GEDUNG ONKOLOGI RUMAH SAKIT UMUM HAJI SURABAYA) - Putri Meyshinta; Nauval Alvian Firmansyah; Minarni Nur Trilita (Racic : Rab Construction Research, 2026)
Hospitals are essential facilities required to maintain structural integrity and operational continuity during seismic events. This study aims to analyze seismic loads and evaluate inter-story drift in the Oncology Building of Haji Surabaya General Hospital to assess structural safety and compliance with earthquake-resistant design requirements. The analysis was conducted using SAP2000 and Microsoft Excel. The research methodology includes the calculation of dead loads, live loads, and seismic loads based on site-specific seismic parameters and local soil characteristics. The results indicate that the eight-story reinforced concrete building with a Special Moment-Resisting Frame system satisfies the required seismic performance criteria. The obtained seismic parameters include a peak ground acceleration (PGA) of 0.3155 g, spectral acceleration parameters Ss of 0.6789 g and S1 of 0.3044 g. Response spectrum analysis yielded SMS and SM1 values of 0.785 and 0.396, respectively, while the design spectral accelerations were determined as SDS = 0.640 and SD1 = 0.570. The fundamental vibration periods of the structure were calculated as T0 = 0.180 s and Ts = 0.890 s, with the building classified as Risk Category IV and Seismic Design Category D. In conclusion, the Oncology Building structure of Haji Surabaya General Hospital meets the seismic performance requirements, with combined modal mass participation ratios of 0.95049 in the X direction and 0.95031 in the Y direction. The structure is considered safe, as the allowable inter-story drift (Δa) exceeds the actual drift values in both directions